Growing Media Affects Broccoli Morpho-Physiological Traits and Mineral Composition in Response to Salt Stress - Roosta, Hamid Reza; Salari, Hadi; Abolghasemi, Reza (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
Among abiotic stresses in vegetable production, salt stress is very important. This study was conducted to introduce suitable growing media to reduce salinity effects in hydroponics. So, the pot culture of broccoli was investigated in a factorial experiment. Here, the effects of six different growing media (100% cocopeat, 25% cocopeat + 75% perlite, 75% cocopeat + 25% perlite, 100% perlite, 50% peat + 50% pumice, and 100% sand) and three salinity levels (0, 100, 150 mM NaCl) on broccoli cv. Sakura were examined. Based on the results, salinity caused a decrease in plant performance. However, different salinity levels had varying effects. When the chlorophyll content and Ca, K, and Fe concentrations in plant leaves decreased as a result of high salt levels, the broccoli yield decreased. The different growing media exhibited highly distinct performances. Due to the substantial interactions between the growing media and salt, it is possible to regulate the media factors to lessen the effects of salinity on plants. Perlite did not support the growth of broccoli, but it did hasten the plants' early flowering times. It was discovered that among the growing media, the optimal medium in both saline and non-saline treatments was 50% peat + 50% pumice. Accordingly, this growing medium is recommended for broccoli production.